Dynamic displacement measurement based on triangle phase modulation without preliminary measurement of half-wave voltage for phase modulator. (24th February 2017) - Tanaka, Yosuke; Kimura, Ryosuke; Ito, Takamasa; Kurokawa, Takashi
Abstract: This paper presents an improved method for our recently proposed dynamic displacement measurement based on triangle phase modulation. The use of deep phase modulation eliminates the need for preliminary measurement of half-wave voltage V π for the phase modulator. We demonstrate displacement measurement with tens-of-nanometer scale taking place within a few micro seconds, where the temporal resolution is 33 ns. A long-term stability is also realized by employing a simple feedback control for the interferometer. The measurement precision is proved to be as high as that in the previously developed system that required careful preliminary measurement of V π .